Quality indicators in colonoscopy: the chasm between ideal and reality - Su Bee Park; Jae Myung Cha (Korean Society of Gastrointestinal Endoscopy, 2022)
Continuous measurement of quality indicators (QIs) should be a routine part of colonoscopy, as a wide variation still exists in the performance and quality levels of colonoscopy in Korea. Among the many QIs of colonoscopy, the adenoma detection rate, average withdrawal time, bowel preparation adequacy, and cecal intubation rate should be monitored in daily clinical practice to improve the quality of the procedure. The adenoma detection rate is the best indicator of the quality of colonoscopy; however, it has many limitations for universal use in daily practice. With the development of natural language processing, the adenoma detection rate is expected to become more effective and useful. It is important that colonoscopists do not strictly and mechanically maintain an average withdrawal time of 6 minutes but instead perform careful colonoscopy to maximally expose the colonic mucosa with a withdrawal time of at least 6 minutes. To achieve adequate bowel preparation, documentation of bowel preparation with the Boston Bowel Preparation Scale (BBPS) should be a routine part of colonoscopy. When colonoscopists routinely followed the bowel preparation protocols, ≥85% of outpatient screening colonoscopies had a BBPS score of ≥6. In addition, the cecal intubation rate should be ≥95% of all screening colonoscopies. The first step in improving colonoscopy quality in Korea is to apply these key performance measurements in clinical practice.